Peran Mediator Dalam Pelaksanaan Mediasi Perkara Perceraian Di Mahkamah Syar’iyah Sigli (Al-Mizan, 2024)
Conflicts in household relationships often lead to divorce when no solution is found, despite efforts for reconciliation. Dispute resolution can be pursued through litigation or non-litigation, with the majority of cases in the Mahkamah Syar’iyah being divorce-related. The author aims to examine the role of mediators in reconciling the disputing parties and the success rate of mediation in divorce cases at the Mahkamah Syar’iyah Sigli. Although mediation aims to achieve reconciliation, success is not always attained. This research uses an empirical juridical approach to analyze the role of mediators in divorce case mediation at the Mahkamah Syar’iyah Sigli. The study is focused solely on mediators and the divorce mediation process. The research method is qualitative, with primary data obtained through direct interviews with mediators, and secondary data from relevant literature. Data collection techniques include literature review, and the analysis is descriptive to present the research findings. Mediation plays a crucial role in resolving divorce disputes at the Mahkamah Syar’iyah Sigli, although it is often hindered by factors such as a lack of public understanding, distrust in the neutrality of the mediator, and the mediator’s limited experience. Solutions include improving mediator capacity through training, adopting a communicative and empathetic approach, and fostering active commitment from both parties to reach a peaceful agreement. The success of mediation heavily depends on the goodwill and active participation of the disputing parties.